Environmental management handbook: volume IV, Managing water resources and hydrological systems - Fath, Brian D.; Jørgensen, Sven Erik (BOCA RATON: CRC, 2021)
"The Environmental Management Handbook is an excellent resource for finding basic knowledge on environmental systems. It reflects an extensive coverage of the field and includes the most important problems and solutions posed to environmental management today. In a very practical way, the handbook demonstrates the key processes and provisions for enhancing environmental management. The experience, evidence, methods, and models used in studying environmental management is presented here in six stand-alone volumes, arranged along the major environmental systems. The chapters are contributed by leading experts from around the globe"--
volume 1. Managing global resources and universal processes -- volume 2. Managing biological and ecological systems -- volume 3. Managing soils and terrestrial systems -- volume 4. Managing water resources and hydrological systems -- volume 5. Managing air quality and energy systems -- volume 6. Managing human and social systems.
Includes bibliographical references and index.
Keywords: Environmental management -- Handbooks, manuals, etc